Handling time in economic evaluation studies. - Unchalee Permsuwan (2018)
BACKGROUND: lime horizon and discounting are important issues in economic evaluation studies and have an impact on the priority of different programs. OBJECTIVE: Provides supporting rational and theories to propose the appropriate discount rate for both cost and effect and time horizon for conducting economic evaluation studies in Thailand. MATERIAL AND METHOD: Describe the theories that explain time horizon for both the cost of a study and its effect. CONCLUSION: The recommended uniform discount rate for both costs and effects at the base case is 3% with a variance in range from 0-6% by sensitivity analysis. The time horizon should be long enough to capture the full costs and effects of the programs.